Typology Of Derivational Systems of The Russian and Uzbek Languages - Burkhanova Gulrukh (Genius Journals, 2021)
One of the basic concepts of linguistic typology is the concept of "type of language". However, it is rather difficult to give its precise and adequate definition. This happens because the very approach of scientists to what should be considered a type of language has not yet been determined, and those criteria that could serve as a reliable basis for determining a particular type of language have not been established either. Considering the Russian and Uzbek languages, we can easily make sure that similar features are found in these languages.
Keywords: Temporal word; level; word; grammatical gender